Validation of the Geriatric Oral Health Assessment Index in complete denture wearers. (5th March 2015) - Campos, J. A. D. B.; Zucoloto, M. L.; Geremias, R. F.; Nogueira, S. S.; Maroco, J.
Summary To perform a validation of the Geriatric Oral Health Assessment Index (GOHAI) for complete denture wearers and present a proposal for estimation of perceived oral health. This is a cross‐sectional study with non‐probabilistic sampling. A total of 211 subjects with a mean age of 62·5 (s.d. = 11·4) years participated, being 169 female. The GOHAI was applied in a personal interview. The construct/convergent/discriminant validity was tested using structural equation modelling. Confirmatory factor analysis was used to verify the fit of three proposals of the GOHAI: three‐factor, one‐factor and second‐order hierarchical models. The stability of the models was evaluated in independent samples. The three‐factor model presented an inadequate fit, and items 3, 4 and 9 were removed. The new structure presented an acceptable fit and strong invariance in independent samples. The convergent, discriminant validity and internal consistency were below adequate. The one‐factor model presented an adequate fit to the sample. Convergent validity was compromised. A strong invariance of the one‐factor model was observed. To calculate the overall scores of the GOHAI factors (three‐factor model) or of the oral health perception (one‐factor model), a matrix of regression weights for each item in the model was presented as a suggestion. We found an adequate fit of the both structures of the GOHAI for denture wearers, but the three‐factor structure was more parsimonious. We suggested considering the weights of the regression model to calculate the overall score of perceived oral health or of its factors in different samples.